2021
DOI: 10.1590/1516-4446-2019-0591
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in borderline personality disorder symptomatology after repetitive transcranial magnetic stimulation of the dorsomedial prefrontal cortex: preliminary results

Abstract: Objective: Current treatment for borderline personality disorder (BPD) involves psychological and pharmacological interventions. However, neuromodulation techniques such as repetitive transcranial magnetic stimulation (rTMS) may positively affect BPD symptomatology. The objective of this study was to evaluate the clinical and neuropsychological effects of rTMS on the dorsomedial prefrontal cortex (DMPFC) in BPD patients. Methods: Fourteen patients with BPD were randomized into two groups (active vs. sham) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…High effects sizes were observed for the changes in Lack of Premeditation and emotion dysregulation, medium effect sizes were observed for changes in Lack of Perseverance and in anxiety and depression levels. The results are consistent with previous studies, specifically the decreased anxiety ( 19 , 22 ), depression ( 14 , 15 , 18 20 , 22 ), impulsivity ( 15 , 19 , 20 ) and affective instability ( 16 ). Overall, rTMS treatment had positive effects on some BPD symptoms including anxiety, depression, emotion dysregulation, and impulsivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…High effects sizes were observed for the changes in Lack of Premeditation and emotion dysregulation, medium effect sizes were observed for changes in Lack of Perseverance and in anxiety and depression levels. The results are consistent with previous studies, specifically the decreased anxiety ( 19 , 22 ), depression ( 14 , 15 , 18 20 , 22 ), impulsivity ( 15 , 19 , 20 ) and affective instability ( 16 ). Overall, rTMS treatment had positive effects on some BPD symptoms including anxiety, depression, emotion dysregulation, and impulsivity.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, rTMS treatment had positive effects on some BPD symptoms including anxiety, depression, emotion dysregulation, and impulsivity. Interestingly, only one study ( 16 ) used high-frequency stimulation of the right DLPFC such as in our study; other studies used low-frequency stimulation of the same area ( 19 ), or high-frequency stimulation of the left DLPFC ( 14 , 15 , 19 , 20 ), or DMPFC stimulation ( 18 , 22 ). Our results are consistent across the previous studies ( 23 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…At least one study showed that more severe baseline depression lowers the response to evidencebased psychotherapies for BPD, such as dialectical behaviour therapy (DBT) 4 . Further, available evidence does not generally support the use Article https://doi.org/10.1038/s44220-022-00003-x severity and depression commonly observed in suicidal individuals with BPD [16][17][18][19] . In this Article, we present the results from an open-label clinical trial investigating the feasibility, and clinical and cognitive effects, of a 5-week course of conjoint MST plus DBT (n = 9) compared with DBT alone (n = 10) in suicidal patients with comorbid BPD and treatment-resistant depression.…”
Section: Articlementioning
confidence: 99%
“…She also had difficulties with self‐esteem and anger management. The second patient was a 20‐year‐old male who had a history of depression and anxiety, low self‐esteem and interpersonal problems 13 …”
Section: Repetitive Tmsmentioning
confidence: 99%